Self-reliance and poverty: Net earnings capacity versus income for measuring poverty - Robert Haveman; Andrew Bershadker (Levy Economics Institute of Bard College, 1998)
The United States' official poverty measure defines the poor in terms of a family's actual, yearly cash income relative to an estimate of the income needed to sustain a minimally acceptable standard of living. An alternative definition, designed to reflect a family's ability to achieve economic independence, would instead rest on its capacity for generating income. Net earnings capacity (NEC) is an indicator of the income a family could earn if all working-age family members work full-time, full-year, at earnings consistent with their age, education, and other characteristics, with an adjustment made for child care costs. NEC is not intended as a replacement for the official measure, but as a supplement. The official measure identifies the population in need of short-term monetary assistance, whereas NEC identifies the population in need of longer-term skill-enhancing assistance in order to become self-reliant. Two general policy approaches to reduce the prevalence of NEC poverty are to increase the level of education and other income-generating characteristics of those with low earnings capacity and to increase the returns they receive for work.
Keywords: 330